Inclusive Physical Activity to Promote the Participation of People with Disabilities: A Preliminary Study - Di Domenico, Felice; D’isanto, Tiziana; Altavilla, Gaetano; D’Elia, Francesca; Raiola, Gaetano (International Journal of Statistics in Medical Research, 2022)
Background: Physical activity brings improvements in the quality of life in all individuals, disabled and non-disabled. There is little evidence in the literature of inclusive physical activity in which disabled and non-disabled people participate at the same level. Objectives: The study aimed to demonstrate the effectiveness of an inclusive training program, structured in such a way as to encourage physical activity for all participants with and without disabilities, in improving body composition, explosive strength, and endurance. Methods: A sample of twenty-four subjects (mean age: 24.09±3.92 years), 12 disabled and 12 non-disabled, was selected. Quantitative input and output data were recruited at 16-week intervals using a battery of tests: anthropometric measurements, Vertec Squat Jump test, and Yoyo Endurance Test. During the 16 weeks, all participants followed an appropriately structured training program in four mesocycle without any differences. Input and output data were compared employing the t-test for dependent samples. Results and conclusions: The results showed statistically meaningful improvements at an alpha level set at 0.05 for the three parameters tested. These results confirmed the effectiveness of the proposed inclusive training protocol on the improvement of the tested parameters in all participants. These strategies didn’t jeopardise the achievement of the overall objectives set; on the contrary, improvements in BMI, explosive strength, and endurance strength of 4.8%, 4.3%, and 56.2% respectively were observed.